The impact of pycnogenol supplementation on plasma lipids in humans: A systematic review and meta‐analysis of clinical trials. (19th November 2018) - Hadi, Amir; Pourmasoumi, Makan; Mohammadi, Hamed; Javaheri, Aftab; Rouhani, Mohammad Hossein
Abstract : The effects of pycnogenol on plasma lipids are controversial. A systematic review and meta‐analysis of clinical trials were conducted to obtain a conclusive result in humans. PubMed, Scopus, and Google Scholar were systematically searched until March 2018, to explore the clinical trials that examined the effect of pycnogenol supplementation on lipid parameters among adult human. Methodological quality of the eligible studies was evaluated using the Cochrane Collaboration's tool. To estimate the effect size, changes in blood lipids were implemented. Results were pooled using a random effects model. Potential sources of heterogeneity were explored by subgroup analysis. A systematic review and meta‐analysis of 14 clinical trials with 1, 065 participants suggested a significant increase in plasma concentration of high density lipoprotein cholesterol (HDL‐C; 3.27 mg/dL; 95% CI [0.19, 6.36]; p  = 0.038). In contrast, plasma levels of total cholesterol (TC; −4.45 mg/dL, 95% CI [−11.24, 2.34]; p  = 0.199), triacylglycerol (TAG; −3.64 mg/dL; 95% CI [−17.89, 10.61]; p  = 0.616), and low density lipoprotein cholesterol (LDL‐C; −3.61 mg/dl; 95% CI [−8.76, 1.55]; p  = 0.171) were not altered. Adjustment for confounding variables was poor in included studies. Also, these studies did not assess dietary lipid intake. The results indicate that pycnogenol supplementation improves levels of HDL‐C; however, the changes in TC, TAG, and LDL‐C were not clinically relevant. Since there are few phytochemicals that have a significant increasing effect on HDL‐C levels, pycnogenol may have important role in prevention of cardiovascular diseases.